Pengembangan Media Marble Maze Untuk Melatih Kemampuan Problem Solving Anak Usia Dini - Rizka, Sitti Muliya; Nasir, Nasir; Arfah, Wahyuni; Nessa, Rahmatun; Suhartati, Suhartati (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
Development Of Marble Maze Media For Training Problem-Solving Skills In Early Childhood. This research aims to produce valid Marble Maze media to enhance problem-solving skills in early childhood, specifically for children aged 4-5 years. The study follows a Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observations, interviews, literature reviews, and questionnaires. The results indicate that the Marble Maze media, which is effective for enhancing problem-solving skills, features labyrinth games with winding paths and sticker challenges. The feasibility of the Marble Maze media, based on validation results from media experts, received a score of 90%, categorizing it as "very valid." Similarly, validation results from material experts also scored 87%, confirming its very valid status. The effectiveness of the Marble Maze media is assessed based on trial results, which indicate that it is very valid. Validation results from both experts confirm that the product is valid.